Toxicology of the cardiovascular system - Siegl, Peter (Henry Stewart Talks, 2011)
Cardiovascular toxicities and adverse events in drug development programs, CV drug removals from market, Scientific perspective, Regulatory perspective, Strategies for minimising risks of CV toxicity in drug development programs, Strategies for managing risks of CV toxicity in drug development programs
Reviewed at 2020/03/19